MENUMBUHKAN RESILIENSI KAUM LANSIA DI SEKOLAH LANSIA TANGERANG - Raja Oloan Tumanggor (PROSIDING SERINA, 2021)
The Covid-19 pandemic has had a major impact on all walks of life, including the elderly. Because of their advanced age, they are very susceptible to various diseases. So when there is a vaccination effort from the government to increase the community's immune system, the elderly become a top priority. In addition to physical health factors, the elderly also experience psychological problems during the current pandemic. They experience loneliness because they can no longer socialize with their families and also with fellow elderly because of physical distancing regulations to stem the transmission of the Covid 19 virus. Feelings of loneliness that cannot be overcome can result in stress. If stress continues, it will certainly affect physical health, which may have been suffering from several diseases. To overcome this problem the Protestant Church community in Western Indonesia (GPIB) the Samaria Tangerang Congregation held various activities called the Elderly School. This Elderly School is filled with various activities such as psychoeducation, training and gymnastics. In this PKM, psychoeducation was held about the resilience of the elderly during the pandemic. Resilience is the ability that individuals have in dealing with pressing problems or situations in life, so they can rise again, and look at problems positively. The goal is to help the elderly to be able to face the problems of life and rise again to meet a better future. The Community Service (PKM) which was carried out through Zoom was attended by 30 elderly and filled with presentations, questions and answers and sharing experiences on how the elderly make peace with the problems in their lives, so that they can motivate other fellow seniors